Designing a new ultra-high strength steel with multicomponent precipitates under material genetic design - Jihang Li; Jialong Tian; Dongping Zhan; Wei Wang; Zhouhua Jiang (Journal of Materials Research and Technology)
Ultra-high strength steels with excellent strength, ductility and toughness have become one of indispensable high-performance structural materials. The development of ultra-high strength steels with higher performance has been widely concerned to break the strength-ductility trade-off. This study proposes a material inverse design strategy that combines material genetic design with thermodynamic calculation to search for new alloys with desirable microstructure and optimal strengthening contributions. Based on the advancement of the ‘Pareto Front’, a new steel with superior properties was successfully screened from 390,625 candidate individuals, which was verified by experiments. The experimental results show that a new steel Fe-0.25C-14.8Ni-17.0Co-2.54Mo-1.56Cr-0.53Al-1.06Cu-0.38V (wt. %) has been successfully developed. After quenching-cryogenic-aging process, the new steel achieved a superior combination of strength, ductility and toughness, with a yield strength of 2.2 GPa, an elongation-to-failure of 10% and a V-notch impact energy of 15 J. Multi-scale microstructure characterization indicates that such superior property synergy arises from the unique microstructure: lath martensite matrix with high-density dislocations and interstitial solid soluble carbon atoms, embedded fine M2C, NiAl and Cu-rich nanoprecipitates. We present an in-depth discussion on the origins of superior strength/ductility/toughness combinations of the new steel to validate the design strategy and provide an accessible pathway exploiting high-performance ultra-high strength steels.